METODE JIGSAW DI MTS.S NU SIBORONG-BORONG DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM - Mardliya Harahap (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Students consider the History of Islamic Culture lesson to be a boring and tedious lesson. This problem occurs because the teacher is not creative enough in learning activities (using the same methods). Therefore, to try to make students learn more actively, think more critically, participate more in the learning process or learning and learning, more interested in learning. Educators (teachers) must be able to condition students, and use the right method, so that students are more interested in the process of learning the History of Islamic Culture. Based on the background of the problem above, the researcher is interested in raising this problem into a study in the form of a written work entitled "Jigsaw Method at MTs.S NU Siborong-Borong in Increasing Student Learning Interest in the Subject of History of Islamic Culture". From the results of the study above, it can be concluded that the application of the jigsaw method can increase students' interest in learning the History of Islamic Culture in class VIII MTs.S NU Siborong-Borong in the 2023/2024 academic year. This is indicated by the results of observations of teacher activities in cycle I reaching 95% experiencing a determination in cycle II of 95%. While the results of observations of student activities in cycle I reached 85% experiencing an increase in cycle II to 95%. As for student learning interest in cycle I, out of 17 students, there were 11 students with a percentage of 64.7%. While in cycle II, out of 17 students, there were 16 students with a percentage of 94.1%. From these data, it shows that using the jigsaw method can increase student learning interest in the subject of Islamic Cultural History Class VIII A MTs.S NU Siborong-Borong in the 2023/2024 academic year.